2018
DOI: 10.1017/jfm.2018.660
|View full text |Cite
|
Sign up to set email alerts
|

Machine-aided turbulence theory

Abstract: The question of whether significant sub-volumes of a turbulent flow can be identified by automatic means, independently of a-priori assumptions, is addressed using the example of two-dimensional decaying turbulence. Significance is defined as influence on the future evolution of the flow, and the problem is cast as an unsupervised machine 'game' in which the rules are the Navier-Stokes equations. It is shown that significance is an intermittent quantity in this particular flow, and that, in accordance with pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 19 publications
2
64
0
Order By: Relevance
“…General reviews can be found in [29,30] We discuss in this section how Monte-Carlo experimentation can be applied to test whether this vortex model is the only possible one for causality in two-dimensional decaying turbulence. The problem and the general procedure are described in [11,31], and there are few differences between the experiments here and in these references. The new material mostly refers to postprocessing the resulting data, and to how conclusions can be drawn from them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…General reviews can be found in [29,30] We discuss in this section how Monte-Carlo experimentation can be applied to test whether this vortex model is the only possible one for causality in two-dimensional decaying turbulence. The problem and the general procedure are described in [11,31], and there are few differences between the experiments here and in these references. The new material mostly refers to postprocessing the resulting data, and to how conclusions can be drawn from them.…”
Section: Introductionmentioning
confidence: 99%
“…Unless otherwise specified, all the cases discussed here have Fourier resolution 256 2 , with Re = q 0 L/ν = 2500, where ν is the kinematic viscosity. Further details can be found in [31]. Figure 2 is a typical initial vorticity field, with the 10×10 grid overlaid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An emerging family of approaches uses various machine-learning techniques such as neural networks to deduce closure models with certain optimality properties from data. In this context we mention the investigations [15,26,34], whereas the state-ofthe-art in this field is discussed in the review papers [12,19,22]. Data-driven machinelearning methods, in addition to other data-driven techniques, have been utilized for computational prediction, modelling, and diagnosis of various turbulent flows [29,33,47].…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…In recent years, machine learning and data science have undergone rapid development thanks to increased data availability, boosted computing power and advanced algorithmic innovations. Many researchers have started to incorporate machine learning and data science techniques into modeling fluid systems (Brunton et al, 2016;Colabrese et al, 2017;Jiménez, 2018;Raissi et al, 2019). For RANS turbulence modeling, the task is to learn a good model for the Reynolds anisotropy tensor and considerable effort has been devoted to it (Tracey et al, 2015;Zhang and Duraisamy, 2015;Ling et al, 2016a,b;Wang et al, 2017;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%